2010
DOI: 10.1007/s00442-010-1696-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of pollen limitation on the coexistence of two dioecious, wind-pollinated, closely related shrubs in a fluctuating environment

Abstract: Elucidating the mechanisms of species coexistence is a crucial goal in ecology. Theory suggests that, when resource abundance fluctuates, coexistence can be achieved if each species in a competing pair is better at exploiting resources at opposite extremes of a fluctuating resource spectrum. Nonetheless, the proximal mechanisms allowing coexistence remain largely unexplored. In a previous paper, we showed that the coexistence of two Atriplex species was facilitated by their varying demographic response (in sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…In the stretches of the riparian corridor with QF, which is the only native tree found at these altitudes (above 3,000 m a.s.l. ; Cázares‐Martínez, Montaña, & Franco, ), the results indicated that the allochthones contributions that reaches the river are relevant. It should be emphasized that the arboreal vegetation cover in the high‐Andes region differs from the mountains at other latitudes, which are dominated by pine and spruce forests (Scarsbrook & Halliday, ).…”
Section: Discussionmentioning
confidence: 85%
“…In the stretches of the riparian corridor with QF, which is the only native tree found at these altitudes (above 3,000 m a.s.l. ; Cázares‐Martínez, Montaña, & Franco, ), the results indicated that the allochthones contributions that reaches the river are relevant. It should be emphasized that the arboreal vegetation cover in the high‐Andes region differs from the mountains at other latitudes, which are dominated by pine and spruce forests (Scarsbrook & Halliday, ).…”
Section: Discussionmentioning
confidence: 85%
“…We have previously shown that temporal variability can contribute to the long‐term coexistence of two species differing in maintenance, growth and reproductive trade‐offs (Verhulst et al , Cázares‐Martínez et al ) because of their contrasting responses at opposite levels of abundance of the limiting resource. The work reported here adds to the evidence of the role of both spatial and temporal stochasticity in resource supply on the ability of a species to subsist (and thus coexists with other species) in two contrasting habitats: by taking advantage of small but predictable resource pulses (summer rain) in all stages of the life cycle at LR, or via sporadic recruitment and faster growth at the expense of a shorter life at HR.These demographic opportunities further shape the species’ niche.…”
Section: Discussionmentioning
confidence: 99%
“…However, if we can assume that populations of larger trees are in an equilibrium stage, spatial point pattern analysis can be an effective approach for the detection of lagged effects of density dependence, by looking at changes in aggregation of each species from early to later life-history stages. This is possible because pollen and seed dispersal limitation, which are quite common in plant communities (e.g., Hubbell et al 1999, Cázares-Martínez et al 2010), may cause spatial aggregation in recruitment (Wright 2002). If there is strong negative density dependence, the degree of conspecific aggregation will decline with increasing size class, due to lower survival of individuals growing in high density patches of conspecifics (Sterner et al 1986; Barot et al 1999; Condit et al 2000).…”
Section: Introductionmentioning
confidence: 99%